Meet Tops British Rail's Management System. (13th February 2019) - Aylen, Jonathan; Gwynne, Bob
Abstract: British Rail made pioneering use of networked computers during the 1970s to manage freight trains. This little known story was presented to the Computer Conservation Society in London in October - Jonathan Aylen (Newcomen Society) and Bob Gwynne (National Railway Museum) report.